2009
DOI: 10.4067/s0717-95022009000400049
|View full text |Cite
|
Sign up to set email alerts
|

Rat Spermatogenesis Damage in Intermittent Hypobaric Hypoxia and the Protective Role of Melatonin: I Cauda Epididymal Spermatozoa

Abstract: At present it is not clear if male fertility is affected by intermittent hypobaric hypoxia (IHH). This is an important issue since a large human population works over 3000 masl. This study analyzes epididymal sperm, in adult Sprague Dawley rats after five cycles of IHH (7 days exposure to 4200 masl in a hypobaric chamber / 7 days at 500 masl). The animals were separated into groups of 8, one group was exposed to hypoxia (7 days), and the others to IHH for one to five cycles. Controls (500 masl) were examined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 29 publications
0
15
2
Order By: Relevance
“…However, in the aforementioned studies melatonin did not have any effect with the doses used in contrary to other reports where melatonin had a protective role in testis and spermatogenesis of rats subjected to intermittent hypobaric hypoxia (Hartley et al, 2009;Bustos-Obregón et al, 2010;Vargas et al, 2011);Ahmad & Haldar (2010) as well as hamsters and rats, where melatonin seems to act directly on Leydig cells to suppress testosterone release in vitro. When administered orally at 10 mg/kg bodyweight, melatonin has been described as a counteracting substance for testis and spermatogenesis damage in rats subjected to intermittent hypobaric hypoxia (Vargas et al, 2011).…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…However, in the aforementioned studies melatonin did not have any effect with the doses used in contrary to other reports where melatonin had a protective role in testis and spermatogenesis of rats subjected to intermittent hypobaric hypoxia (Hartley et al, 2009;Bustos-Obregón et al, 2010;Vargas et al, 2011);Ahmad & Haldar (2010) as well as hamsters and rats, where melatonin seems to act directly on Leydig cells to suppress testosterone release in vitro. When administered orally at 10 mg/kg bodyweight, melatonin has been described as a counteracting substance for testis and spermatogenesis damage in rats subjected to intermittent hypobaric hypoxia (Vargas et al, 2011).…”
Section: Discussioncontrasting
confidence: 51%
“…for 5 days caused an increase in lipid peroxidation in the plasma of rats (Kumar et al, 1999). It has been previously shown that melatonin can also protect tissues from oxidative damage (e.g: testicles) under intermittent hypobaric hypoxia conditions (Bustos-Obregón et al, 2010;Hartley et al, 2009). The aim of this study was to evaluate the protective effect of melatonin in several organs, such as heart, lung, kidney, and reproductive system as testis and epididymis in animals exposed to IHH and therefore exposed to oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was found that the expression of glutathione reductase enzyme was lower in both organs with respect to control, but in epididymis, the expression and GR activity was greater (Farias et al, 2010). It have been also described that melatonin (10 mg kg À1 body weight) counteracted the testis and spermatogenesis damage in rats subjected to intermittent hypobaric hypoxia (Hartley et al, 2009;Bustos-Obregon et al, 2010). However, our results showed that melatonin had no protective effect in testis and epididymis damaged (Farias et al, 2012).…”
Section: Antioxidants For Spermatogenesis Under Intermittent Hypobaricontrasting
confidence: 82%
“…Spermatozoa are cells particularly susceptible to oxidative stress given their limited content of antioxidants (Aitken & Curry, 2011), and several models of hypoxia exposure have shown to produce DNA damage in sperm cells (Hartley, Castro-Sanchez, Ramos-Gonzalez, & Bustos-Obregon, 2009). Our results showing reduced expression of OGG1 enzymes in CHH suggest that attenuation of DNA repair mechanisms may contribute to the DNA damage observed.…”
Section: Resultsmentioning
confidence: 99%